2017
DOI: 10.1371/journal.pone.0174069
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of microbial communities and suppressiveness of Trichoderma fortified composts for pepper seedlings infected by Phytophthora nicotianae

Abstract: The understanding of the dynamic of soil-borne diseases is related to the microbial composition of the rhizosphere which is the key to progress in the field of biological control. Trichoderma spp. is commonly used as a biological control agent. The use of next generation sequencing approaches and quantitative PCR are two successful approaches to assess the effect of using compost as substrate fortified with two Trichoderma strains (Trichoderma harzianum or Trichoderma asperellum) on bacterial and fungal commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 56 publications
1
19
0
Order By: Relevance
“…In addition to rhizosphere colonization, nutrient uptake facilitation and plant growth promotion (Hermosa et al, 2012;Samolski et al, 2012), the application of Trichoderma strains may also affect the soil bacterial and fungal communities in a pH-and N supply dependent manner, respectively (Zhang et al, 2018). It has been reported that biofertilizers based on Trichoderma strains when used alone or in combination with organic fertilizers (compost) provoke changes in the rhizosphere microbial community of crop plants (Zhang et al, 2013;Pang et al, 2017;Ros et al, 2017;Qiao et al, 2019). Specifically, Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to rhizosphere colonization, nutrient uptake facilitation and plant growth promotion (Hermosa et al, 2012;Samolski et al, 2012), the application of Trichoderma strains may also affect the soil bacterial and fungal communities in a pH-and N supply dependent manner, respectively (Zhang et al, 2018). It has been reported that biofertilizers based on Trichoderma strains when used alone or in combination with organic fertilizers (compost) provoke changes in the rhizosphere microbial community of crop plants (Zhang et al, 2013;Pang et al, 2017;Ros et al, 2017;Qiao et al, 2019). Specifically, Trichoderma spp.…”
Section: Introductionmentioning
confidence: 99%
“…While through Trichoderma, ISR is not only induced by the interaction of the plant with Trichoderma, but is also initiated by pathogens (Djonovic et al, 2006). Thirdly, fungi stimulated their presence both by compost and mulch together with Trichoderma may offer the suppression on the disease (Ros et al, 2017). In the shallot treated with Trichoderma, the population in soil and colonization, especially in root tissues of fungi other than Trichoderma, tended to be higher than untreated shallot.…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, Retention of compost in the soil may reduce runoff and erosion, improves soil physical characteristics and nutrient-supplying capacity, increases soil organic matter content and microbial biomass, and reduce nutrient losses (Bhupinderpal- Singh and Rengel, 2007). Further, the incorporation of compost with useful microbes has shown to offer more disease suppression than just by using single compost or beneficial microorganism (Ros et al,2017;Rosmana et al, 2018a). Then mulches are used to cover the soil surface and made from organic or synthetic materials (Chalker-Scott, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, besides obtaining high-value protein-rich functional food product from the bioconversion of crop residues by mushroom fungi (Chang 2008), farmers can also get value-added compost for their farms to enhance crop production and soil fertility. Fortification of raw compost with plant growth-promoting bacteria and biocontrol agents like Trichoderma harzianum potentially enhance suppressiveness of soil-borne diseases and efficacy of compost microbiota against pathogenic diseases (Pugliese et al 2011;Ros et al 2017). Mushroom production is of high economic significance in many parts of the world (Marshall and Nair 2009;Zhang et al 2014) and compost fortified with beneficial microorganisms also has potentials of enterprising (Awad and Khaled 2012;Sarkar and Chourasia 2017).…”
Section: Breakdown Of Cellulose and Hemicellulosesmentioning
confidence: 99%